Influence of Just In Time Toward Corporate Performance: Mediating Role Of Total Quality Management - Miftakul Huda; Nani Hartati; Wiji Safitri; Yoga Religia (DEAL: International Journal of Economics and Business, 2023)
Industry in Indonesia faces challenges that are not easy. Companies are required to be able to increase their competitive advantage, both in the domestic and global markets. Companies are trying to implement various management systems, including management systems, including Just in Time (JIT) and Total Quality Management (TQM) in order to improve company performance. This study aims to: 1) determine and analyze the effect of just in time on total quality management. 2) determine and analyze the effect of total quality management on operational performance, 3) determine and analyze the effect of just in time on operational performance. The type of research is causal associative. The data used is primary data obtained through questionnaires were prepared with closed questions using a semantic differential scale. The number of samples used was 270 and the regression analysis used the AMOS computer program. The results state that just in time has a positive effect on total quality management. Total Quality management has a positive effect on operational performance. Just in time has a positive effect on operational performance, but the indirect effect on operational performance through total quality management becomes stronger.